Development of Avocado oil Nanoemulsion Hydrogel using Sucrose Ester Stearate - Ahmad M. Eid, Nagib A. Elmarzugi, Hesham A. El-Enshasy (Journal of Applied Pharmaceutical Science, 2013)
Nanoemulsion is submicron sized emulsion typically in the range of 20-200 nm. Avocado oil is often used in herbal skin care. The aim of this study was to characterize nanoemulsion hydrogel prepared using avocado oil and sucrose ester stearate as surfactant. The nanoemulsion hydrogel were prepared by nanophase emulsification technique. These formulations were examined using zetasizer to determined the mean diameter of dispersed oil droplets, polydispersibility index (PDI) and zeta potential. Moreover viscosity of the prepared nanoemulsion hydrogel were studied. The results reveled that nanoemulsion prepared with 60% w/w oil, 24% w/w glycerol and 16% w/w surfactant showed droplets size below 200 nm with good polydispersibility index and zeta potential < -30 mV. The optimum formulation of nanoemulsion was prepared in the form of nanoemulsion hydrogel using carbopols 934 and 940. The results of the viscometer for the nanoemulsion hydrogel showed that the storage modulus (G’) which describes the elasticity of the component were greater than the loss modulus (G”) values which reveals the viscosity of the component.
Keywords: Avocado oil, nanoemulsion, sucrose ester, hydrogel.